Pilus-Mediated Adherence of Haemophilus influenzae to Human Respiratory Mucins - Kubiet, Martin (American Society for Microbiology, 2000)
Haemophilus influenzae, especially the nontypeable strains, are among the most common pathogens encountered in patients with chronic lung disease and otitis media. We and others have demonstrated that respiratory isolates of nontypeable H. influenzae bind to human mucins, but the mechanism of binding is not entirely clear. We have therefore examined the role of pili in the adherence of both type b and nontypeable H. influenzae to human respiratory mucins. We used isogenic H. influenzae strains with a mutation in the structural gene for pilin (hifA), a laboratory H. influenzae strain transformed with a type b pilus gene cluster (from strain C54), antibodies raised against H. influenzae HifA, and Escherichia coli strains carrying a cloned type b pilus gene cluster (from strain AM30) in these studies. All bacteria lacking HifA or the pilus gene cluster had decreased adherence of piliated H. influenzae to mucins, and Fab fragments of anti-HifA antibodies inhibited the adherence. E. coli strains carrying the cloned type b pilus gene cluster were six to seven times more adhesive than strains carrying the vector. The role of other putative adhesins was not examined and thus cannot be excluded, but these studies support a role for pili in the binding of H. influenzae to human respiratory mucins.